Intermission [videorecording (DVD)] - Crowley, John, 1969-; Henderson, Shirley; Macdonald, Kelly, 1976-; Meaney, Colm, 1953-; Murphy, Cillian, 1976-; Farrell, Colin, 1976- (MGM Home Entertainment, 2004)
In the suburbs of Dublin, more than a dozen strangers find their paths colliding in sometimes violent, sometimes absurd ways.